Gastroprotective effects of the isopropanol extract of Artemisia princeps and its gastroretentive floating tablets on gastric mucosal injury - Kim Joo-Il; Park Sang-Wook; Lim Jhong-Jae; Sohn Se-Il; Shin Ji-Su; Park Sang Cheol; Jang Young Pyo; Chung Eun Kyoung; Lee Hong-Woo; Lee Kyung-Tae (Acta Pharmaceutica)
In this study, we investigated the gastroprotective effect of an isopropanol extract from the aerial parts of Artemisia princeps (IPAP) and developed a gastroretentive floating tablet of IPAP (IPAP-FR) for maximized local gastroprotective effects. Pre-treatment with IPAP ameliorated the gastric mucosal hemorrhagic lesions in ethanol/HCl- or indomethacin- treated rats. IPAP decreased mucosal hemorrhage of gastric ulcers induced by ethanol or indomethacin plus pyloric ligation in rats. The optimized floating tablet, IPAP-FR, floated on medium surface with more sustained eupatilin release compared to the non-floating control tablet. X-ray photographs in beagle dogs showed that IPAPFR was retained for > 2 h in the stomach. In the ethanol-induced gastric ulcer rat model, the gastric hemorrhagic lesion was improved more substantially with IPAP-FR compared to the non-floating control tablet. Based on these data, our data suggest that IPAP-FR has an improved therapeutic potential for the treatment of gastric ulcer.